Hypomagnesemia in Pre-Renal Acute Kidney Injury Patients with Non-Recovery of the Renal Functions - Hafeez, Zahid; Hafeez, Rana Shahid; Ahmad, Fawad; Anwar, Wasif; Matee, Sumeera (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the hypomagnesaemia frequency in pre-renal acute kidney injury (AKI) patients with non-recovery of renal functions. Study Design: Cross-sectional study. Place and Duration of Study: Al-Noor Specialist Hospital Holy Makah, Saudi Arabia, from Jul 2014 to Jan 2015. Methodology: A total of 150 acute kidney injury patients qualifying the inclusion/exclusion criteria were enrolled in this study. Serum magnesium (Mg) levels were measured for all the patients. Serum magnesium level <0.70 mmol/L (<1.7 mg/dL) was labeled as hypomagnesaemia. Results: The mean age of the patients was 51.64 ± 13.61 years, with 31% males and 69% females. Hypertension was present in 58 (38.7%) patients, 38 (25.3%) patients were obese, and hypomagnesaemia was present in 25% patients. A statistically insignificant difference was found between age of patients (p=0.086) and gender (p=0.970). Conclusion: Our study showed that in patients with acute kidney injury with non-recovery of renal functions, the rate of hypomagnesaemia is quite high. Therefore patients with non-recovery should be screened for magnesium levels in future acute kidney injury.